Effect of mikorizha and granting planting media composition on oil palm nurseries on pre nursery - Fadli Azhari Harahap; Nini Rahmawati; Rosita Sipayung (Universitas Sumatera Utara, 2015)
The growth of seedlings in the field in very determined by the growth of plants in the nursery.Planting media is the one factors that affect the growth of plants in the nursery. Therefore, by givingmikorizha and composition of the planting media is expected can increase the growth of oil palmnurseries in pre nursery. This research was conducted in screen house af Faculty AgriculturalUniversity of Sumatera Utara with altitude ± 25 meters from sea surface from April-July 2014, usedrandomized block design with two factors. The first factor is composition of planting media (sludge+ ultisol) with four levels (0% + 100%) (S0); (25% +75%) (S1); (50% + 50%) (S); (75% + 25%)(S3) and the second factor is mikorizha with three levels 0 (M0); 5 (M12); 10 g/plant (M). Parameterobserved was plant height, stem diameter, number of leaves, total leaf area, leaf greenes, degree ofinfection, root volume, shoof dry weight root dry weight. The result of this research showed that useof planting media composition significantly effect to plant height parameters 6-12 weeks afterplanting, stem diameter 6-12 weeks after planting, number of leaves 6,7,8,10,11 weeks afterplanting, total leaf area, green leaf, degree of infection, root volume and plant dry weight.Mikorizha treatmen is significantly effect the degree of infection parameters. Interaction ofcompositition planting media and mikorizha significantly effect on plant height at 6 weeks afterplanting and degree infection.Keywords: mikorizha, sludge, ultisol, palm oil 2